(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
The influence of synthetic amino acids and peptides on the growth of Pseudomonas aeruginosa multidrug resistant strains isolated from soil has been studied. All investigated strains were sensitive to (S)-β-[4-allyl-3-(furan-2-yl)-5- -thioxo-1,2,4-triasol-1-yl]-α-alanine, (S)-β-[4-allyl-3-(2’-chlorophenyl)-5-thioxo-1,2,4-triazol-1-yl]-α-alanine, dipeptide N-formyl-methionyl-(S)-β-[4-allyl-3-(2’-chlorophenyl)-5-thioxo-1,2,4-triasol-1-yl]-α-alanine and tripeptide alanyl-glycyl-(S)-β-[4-allyl-3-(pyridin-4’-yl)-5-thioxo-1,2,4-triasol-1-yl]-α-alanine. Dipeptide alanyl-(S)-β-[4-allyl-3-(pyridin-4’-yl)-5-thioxo-1,2,4-triazol-1-yl]-α-alanine demonstrates the strongest effect on the growth of P. aeruginosa strains 9311 (resistant to beta-lactams) and 9211 (resistant to beta-lactams and chloramphenicol), but has no influence on the P. aeruginosa 5249 (resistant to all antibiotics used in this study).